Evaluasi Guru dalam Pembelajaran Kurikulum Al-Islam Kemuhammadiyahan dan Bahasa Arab (ISMUBA) di Sekolah - Riska Riska; Henro Widodo (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
The purpose of this study was to see and find out the teacher's evaluation of learning the Al-Islam Kemuhammadiyahan and Arabic Language (ISMUBA) curriculum at the Muhammadiyah Charity Business School of SD Muhammadiyah 1 Palopo. The research method used is qualitative research with a phenomenological approach. Informants were selected using snowball sampling. While the subjects in this study were 4 informants as ISMUBA teachers. Data collection techniques are using observation, interviews and documentation. The interviews used were through in-depth interviews using unstructured interviews in order to obtain deep information. The data analysis technique used begins with reduction, presentation and conclusion. Results (1) the implementation of the ISMUBA curriculum has gone well and also facilitated the process of making learning tools carried out by Al-Islam Kemuhammadiyahan and Arabic Language teachers, (2) the implementation of the ISMUBA curriculum has limited time which has not been maximized in each subject taught to students , as well as a lack of teacher training (debriefing) in implementing the curriculum so that teachers need more training, especially understanding and learning methods of ISMUBA, (3) lack of infrastructure and praga tools in several subjects so that they are not optimal in providing practice or applying ISMUBA values, (4) the need for advanced training or ISMUBA curriculum workshops, either sustainable or structured, to make it easier for students to understand and practice related to the Al-Islam Kemuhammadiyahan and Arabic curricula.